(En) act your age! Marketing and the marketization of history in young SMEs. (8th September 2021) - Weatherbee, Terrance; Sears, Donna
Abstract : Purpose: This paper aims to examine how wineries used history in their marketing communications to overcome the liability of newness in a settled field that valorizes duration and longevity. Design/methodology/approach: A multiple-case study investigated the treatment of history in marketing by young wineries in a new wine region. Data included interviews, site visits and marketing communications. Findings: Wineries worked to communicate stakeholder legitimacy and authenticity by constructing organizational histories through bricolage, communicating history in symbolic, material and practice forms. Research limitations/implications: Young organizations can communicate field legitimacy and projections of organizational and product authenticity through constructed histories. Results may not be generalizable to other jurisdictions as wine marketing is normatively subject to government regulation. The importance of history in marketing communications also varies across sectors. Practical implications: Young businesses in sectors where tradition, place and longevity are venerated can establish authenticity and legitimacy through the marketization of history by following practices that demonstrate adherence to tradition and making thoughtful choices in the construction of the symbolic and material aspects of their organizations. Originality/value: This study demonstrates that new/young organizations can use bricolage to create their own marketized histories as proxies for age.